Brain Abscess Caused by Nocardia farcinica and Diagnosed by Metagenomic Next-Generation Sequencing: A Case Report - Yang, Jianhua; Xie, Shuhua; Li, Junda; Xia, Han; Liu, Xianghong (Frontiers in Medicine, 2022)
Background：Brain abscesses caused by Nocardia farcinica are rare and difficult to diagnose. Previous literature describing brain abscesses caused by Nocardia species has been diagnosed by conventional diagnostic methods, such as positive blood culture, positive brain abscess aspirates of Nocardia spp., presence of nocardia organisms on histopathology of the excised brain specimens. We report a case of brain abscess of Nocardia farcinica diagnosed by metagenomics next-generation Sequencing (mNGS). Case presentation: We report a case of a 58-year-old man with brain abscess caused by Nocardia farcinica. The patient had a history of pemphigus and required long-term methylprednisolone administration. No pathogen was detected in blood culture, cerebrospinal fluid (CSF) culture and fast-acid staining. mNGS identified Nocardia farcinica in the CSF. The patient’s symptoms and signs were significantly improved after changing the antibiotics accordingly using sensitive antibiotics. Conclusion: mNGS is helpful for early diagnosis and subsequent treatment of Nocardia associated meningitis and encephalitis, avoiding brain surgery. Early and accurate diagnosis and prompt antibiotic treatment reduced the mortality.